2011
DOI: 10.3354/meps08929
|View full text |Cite
|
Sign up to set email alerts
|

Assortative interactions and leadership in a free-ranging population of juvenile lemon shark Negaprion brevirostris

Abstract: For marine predators there is a paucity of studies on social behaviour, and even fewer studies have quantified interactions between individuals. In the present study, we looked at the social structure and leadership of free-ranging juvenile lemon shark Negaprion brevirostris in a known aggregation site, Bimini, the Bahamas. Observations of these sharks were made from towers placed in a mangrove inlet, where clear, shallow, protected waters made it possible to record group compositions of externally colour-code… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 55 publications
1
61
0
Order By: Relevance
“…Gallagher et al (2014) reported oceanic whitetip swimming in 'nose-to-tail' formation at CI during spring and speculated that this could be related to courtship (Gallagher et al 2014). However, this be havior was observed in all-female groups, and other studies have observed similar behavior in immature sharks (Guttridge et al 2011).…”
Section: Introductionmentioning
confidence: 49%
“…Gallagher et al (2014) reported oceanic whitetip swimming in 'nose-to-tail' formation at CI during spring and speculated that this could be related to courtship (Gallagher et al 2014). However, this be havior was observed in all-female groups, and other studies have observed similar behavior in immature sharks (Guttridge et al 2011).…”
Section: Introductionmentioning
confidence: 49%
“…This area has been the location for a series of studies investigating aspects of juvenile lemon shark behavioural ecology. The sharks use the area daily and are regularly observed to aggregate at and around the high tide (Guttridge et al 2010(Guttridge et al , 2011. …”
Section: Study Sitementioning
confidence: 99%
“…1b). Over a 2 yr period, a total of 58 juvenile lemon sharks (n = 25 females, n = 33 males; TL = 79 ± 12.3 cm, mean ± SD) were caught every 3 to 4 mo (some repeatedly) through seine and gill netting (Guttridge et al 2011). Briefly, all sharks were sexed, measured (pre-caudal, total length), tagged with a passive integrated transponder (PIT, Destron Fearing ® ) and colour-code tagged through the first dorsal fin (T-bar anchor tag, Floy Tag ® ) to enable individual identification using mono-, bi-or tri-coloured tags.…”
Section: Direct Observationsmentioning
confidence: 99%
See 2 more Smart Citations